HUBUNGAN PENGETAHUAN TENTANG SANITASI LINGKUNGAN DENGAN PERILAKU PENCEGAHAN PENYAKIT DEMAM BERDARAH DANGUE (DBD) (Studi Korelasi pada Ibu Rumah Tangga di Penjaringan, Jakarta Utara) - Adi Setyo Pranoto (FT-USNI, 2021)
This study aims to examine the relationship between knowledge about environmental sanitation and the prevention behavior of dengue hemorrhagic fever (DHF) (a study on housewives in Penjaringan, North Jakarta). The research method used is a survey with a quantitative approach and an explanation format. Data analysis used t-test and simple linear regression. The research location is in Penjaringan Village, North Jakarta. This research was conducted from June to November 2019. The population of this study were all housewives in Penjaringan Village, North Jakarta. The total sample size was 92 housewives residing in RT 15 and RT 17 Kelurahan Penjaringan, North Jakarta. The sampling technique used in this study was simple random sampling. The results of the research on the regression equation for knowledge about environmental sanitation on the prevention of dengue fever are . = 43.16 + 1.38X. The result of the calculation of the value of r (only) is 0.271; r table value of 0.205; so that r count> r table. The t test is proven by t count> t table, namely 2.671> 1.986; It can be interpreted that there is a significant relationship between knowledge about environmental sanitation and the behavior of preventing dengue hemorrhagic fever. The results of the calculation of the coefficient of determination (Kd) (r) 2 = 0.074 (7.4%), meaning that the relationship between knowledge about environmental sanitation and the behavior of prevention of dengue hemorrhagic fever is 7.4%. The conclusion of this research shows that there is a positive and significant relationship between knowledge about environmental sanitation and the behavior of preventing dengue fever (DHF). Therefore the increasing knowledge about environmental sanitation, the more behavioral prevention of dengue hemorrhagic fever (DHF) will increase.